SUSHI : SEBUAH TRADISI DALAM MODERNITAS - Sri Wahyu Istana Trahutami (Diponegoro University, 2018)
(Title: Sushi: Tradition in Modernity) Rice and fish are central to Japanese cuisine and the two come together perfectly in sushi. Sushi has become a favourite food throughout the world. Nigirizushi is the most famous sushi of all. Nigiri means “press in the hand” and zushi means “sushi”. Nigirizushi is a clump of sushi rice pressed together with a topping that is usually raw fish. Traditional sushi takes along time and much effort to make. Japanese cuisine would not be complete without sushi. Edomae topping benefits from many long years of innovations in preparation methods all with the aim of achieving a balance, a harmony between the rice an the topping and the waonderful taste wich that harmonius balance can give.Keywords : sushi; nigirizushi; Japanese cuisine; edomae zushi